The international public policy exception: a comparative study of the Spanish and German systems in divorce cases - Schweinbach, Anna Pauline; Carrizo Aguado, David (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
In this paper, a legal and jurisprudential introspection of international public order is carried out in cases of divorce with a foreign element from a comparative legal approach between the Spanish and German regimes in the face of the difficult, but growing coexistence with institutions of the Islamic world, as it happens with repudiation. Issues are addressed, essentially, on applicable law and recognition of foreign divorces, with special consideration of the consequences that this entails in the face of the harmonization of European private international law. Due to the material exclusion of private divorce, for the sake of Regulation (EU) 1259/2010, the repudiation is governed by clauses of international public order of different legal natures. His questioned art. 10, applicable by reference in Spain, implies a relaxation of the criteria traditionally held, facilitating its invocation in the face of repudiation, while its validity in Germany reduces the use of the figure.